3D Organization of Dysprosium Cubanes. Issue 34 (11th October 2013) - Yi, Xiaohui; Bernot, Kevin; Calvez, Guillaume; Daiguebonne, Carole; Guillou, Olivier
Abstract: The reaction of isonicotinic acid N ‐oxide and Dy(NO)3 · 6H2 O under aerobic conditions leads to the formation of a porous lanthanide, a cubane‐based 3D edifice of the formula [Dy4 (μ3 ‐OH)3 (μ3 ‐O)(NOPyCOO)6 (OH)(H2 O)3 · (DMF)3 (H2 O)12 ]∞ (NOPyCOO = pyridine‐4‐carboxylate N ‐oxide). Crystal structure investigations show that the [Dy4 (μ3 ‐OH)3 (μ3 ‐O)] cubane cores are interconnected by organic ligands to form an extended porous structure. Thermogravimetric analyses and temperature‐dependent X‐ray diffraction analyses evidence that the compound is stable upon dehydration/desolvatation up to 200 °C. Calculations for the N2 kinetic radius afford a void volume of 3603 Å 3 per unit cell (33.8 %) and a potential porosity of 1400 m 2  g –1 . The large pores can potentially host molecules with a projected surface area as large as 20 Å 2 into a large pore volume (600 Å 3 ). Moreover, the onset of a slow magnetic relaxation has been observed and rationalized by a comparison with closely related 0D and 2D compounds. Abstract : [Dy4 (μ3 ‐OH)3 (μ3 ‐O)(NOPyCOO)6 (OH)(H2 O)3 · (DMF)3 (H2 O)12 ]∞ (NOPyCOO = pyridine‐4‐carboxylate N ‐oxide) is a lanthanide‐based coordination polymer with large three‐dimensional channels and with potentially high surface areas. It also exhibits the onset of a weak in‐field single‐molecule‐magnet behavior.